Students' Behavioural Responses to a Fallback Option: Evidence from Introducing Interim Degrees in German Schools - Natalie Obergruber; Larissa Zierow (Institute of Labor Economics (IZA), 2018)
Without a school degree, students can have difficulty in the labor market. To improve the lives of upper-secondary school dropouts, German states instituted a school reform that awarded an interim degree to high-track students upon completion of Grade 9. Using retrospective spell data on school and labor market careers from the National Educational Panel Study (NEPS), our difference-in-differences approach exploits the staggered implementation of this reform between 1965 and 1982. As intended, the reform reduced switching between school tracks. Surprisingly, it also increased successful high-track completion, university entrance rates, and later income, arguably by reducing the perceived risk of trying longer in the high-track school.
Keywords: I20; I24; I28; 330; school dropout; school degree; school tracking